Mesenchymal stem cells‐derived exosomes ameliorate intervertebral disc degeneration through inhibiting pyroptosis - Zhang, Jingwei (J Cell Mol Med, 2020)
Mesenchymal stem cell (MSCs)‐based therapies have shown a promised result for intervertebral disc degeneration (IVDD) treatment. However, its molecular mechanisms remain unclear. Exosomes involve cell‐cell communication via transference of its contents among different cells, and the present potential effect on cell death regulation. This study aimed to investigate the role of MSCs‐derived exosomes on IVDD formation. Here, we first found the NLRP3‐mediated nucleus pulposus cell (NP cell) pyroptosis was activated in the IVDD mice model and lipopolysaccharide (LPS)‐induced model. However, MSCs treatment could inhibit NP cell pyroptosis in vitro. We then isolated MSCs‐derived exosomes by differential centrifugation and identified the characteristics. Secondly, we investigated the function of MSCs‐derived exosomes on LPS‐induced NP cell pyroptosis. Finally, we presented evidence that MSCs‐derived exosomal miR‐410 was a crucial regulator of pyroptosis. Results showed that MSCs‐derived exosomes play an anti‐pyroptosis role by suppressing the NLRP3 pathway. Moreover, it suggested that this effect was attributed to miR‐410, which was derived from MSCs‐exosomes and could directly bind to NLRP3mRNA. In conclusion, for the first time, we demonstrated that MSCs‐exosome treatment may inhibit pyroptosis and could be a promising therapeutic strategy for IVDD.